Antioxidative effect of metformin on valproic acid induced hepatoxicity in male rats - Intesar Tarik Numan; Nadia Hameed Mohamed; Zainab Khalid Ali (College of Pharmacy / Mustansiriyah University, 2022)
Metformin is 1,1-dimethylbiguanide hydrochloride, is the first-line therapy for type 2 diabetes. Additionally, several studies focused on the role of metformin in antioxidant activities for the treatment of hepatic disorders. The experimentally    -based result on valproic acid's liver injury, a front-line medicine for the treatment of epilepsy, attracted a lot of interest. As a result, the effect of metformin on valproic acid-induced redox disturbances in rat hepatic tissue was studied. metformin at 250 mg/kg dose was administered via oral gavage for 30 days, and valproic acid at a dose of 400 mg/kg was administered by intraperitoneal route starting from the twenty-second day of the experiment, for eight days to induce hepatotoxicity. Treatment with metformin reduced valproic acid-enhancing alanine aminotransferase, aspartate aminotransferase activities. Tissue levels of malondialdehyde in the liver tissue of valproic acid-treated rats significantly increased (P-value < 0.05) whereas glutathione decreased. The coadministration of metformin with valproic acid significantly decreased the malondialdehyde levels and increased glutathione levels (P-value < 0.05). Finally, metformin protected rats from valproic acid-induced hepatotoxicity, improved antioxidant status, and reduced hepatic oxidative stress.